Firm climate risk, risk management, and bank loan financing - Huang, Henry He; Kerstein, Joseph; Wang, Chong; Wu, Feng (Harry) (Strategic Management Journal, 2022)
Abstract Research Summary We estimate firm‐level physical risk from climate change based on managerial evaluation and firms' exposure to climate hazard events and find that climate risk results in unfavorable corporate financing terms related to bank loans (higher interest paid, higher likelihood of being required to collateralize the loan, and greater number of covenant constraints). Firms that take measures aimed at managing climate risk, including corporate climate strategy, board‐level governance, specific or integrated process to cope with climate change, climate opportunities, and climate policy involvement, are able to mitigate the negative impact of climate risk on loan contracting. We further find that higher climate risk level is associated with inferior financial performance and higher default probability, which potentially lead to more stringent loan terms. Managerial Summary We examine how a firm's exposure to climate risk affects its financing terms from bank loans. Climate risk exposure is assessed by firm managers and also reflects the degree to which the firm is subject to climate‐induced natural disasters. The results show that if exposed to higher climate risk, which hurts financial performance and heightens default likelihood, firms face higher interest rates and more stringent collateral and covenant constraints when borrowing from banks. Nevertheless, firm managers could significantly mitigate this adverse climate impact on loan financing by integrating climate change into business strategy, having the board take direct responsibility for climate change issues, establishing a climate change‐focused risk management process, seeking business opportunities from climate change, and engaging in activities that influence climate policies.